2003
DOI: 10.1523/jneurosci.23-02-00403.2003
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Type 1 Inositol (1,4,5)-Trisphosphate Receptor Function by Protein Kinase A and Protein Phosphatase 1α

Abstract: Type 1 inositol (1,4,5)-trisphosphate receptors (InsP3R1s) play a major role in neuronal calcium (Ca2+) signaling. The InsP3R1s are phosphorylated by protein kinase A (PKA), but the functional consequences of InsP3R1 phosphorylation and the mechanisms that control the phosphorylated state of neuronal InsP3R1s are poorly understood. In a yeast two-hybrid screen of rat brain cDNA library with the InsP3R1-specific bait, we isolated the protein phosphatase 1alpha (PP1alpha). In biochemical experiments, we confirme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
172
1

Year Published

2004
2004
2011
2011

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(188 citation statements)
references
References 67 publications
15
172
1
Order By: Relevance
“…tuted into lipid bilayers has reported a similar increase in InsP 3 R sensitivity to InsP 3 but that the bell-shaped Ca 2ϩ sensitivity of channel opening is not altered following phosphorylation of the InsP 3 R-1 (20). These findings suggest that modulation of the Ca 2ϩ sensitivity of channel activity is unlikely to account for the increased apparent sensitivity of the receptor, at least in this form of the InsP 3 R-1.…”
Section: Sensitivity Of S2ϩ Insp 3 R-1 and Phosphorylation Site Mutants-mentioning
confidence: 85%
“…tuted into lipid bilayers has reported a similar increase in InsP 3 R sensitivity to InsP 3 but that the bell-shaped Ca 2ϩ sensitivity of channel opening is not altered following phosphorylation of the InsP 3 R-1 (20). These findings suggest that modulation of the Ca 2ϩ sensitivity of channel activity is unlikely to account for the increased apparent sensitivity of the receptor, at least in this form of the InsP 3 R-1.…”
Section: Sensitivity Of S2ϩ Insp 3 R-1 and Phosphorylation Site Mutants-mentioning
confidence: 85%
“…PKA phosphorylates InsP 3 R1 at two sites, Ser-1589 and Ser-1755 (31)(32)(33)(34)(35)(36). PKA phosphorylation activates InsP 3 R1 by increasing the sensitivity of InsP 3 R1 to activation by InsP 3 (35,(37)(38)(39). In previous biochemical studies, we discovered direct association of neuro-nal InsP 3 R1 with PP1␣ (39) and showed that the InsP 3 R1⅐AKAP9⅐PKA complex is formed in the brain (40).…”
Section: From the Department Of Physiology University Of Texas Southmentioning
confidence: 99%
“…PKA phosphorylates InsP 3 R1 at two sites, Ser-1589 and Ser-1755 (31-36). PKA phosphorylation activates InsP 3 R1 by increasing the sensitivity of InsP 3 R1 to activation by InsP 3 (35,(37)(38)(39). In previous biochemical studies, we discovered direct association of neuro-* This work was supported by the Robert A. Welch Foundation, the Hereditary Disease Foundation, and National Institutes of Health Grant R01 NS38082 (to I.…”
mentioning
confidence: 99%
“…The interaction of specific accessory proteins has been demonstrated to either positively or negatively regulate IP 3 R opening, with consequent alteration of cellular Ca 2+ signals (e.g. [25,26]). Although most of the data exploring IP 3 R-binding proteins has been derived from studies of neuronal IP 3 Rs, it is likely that cardiac IP 3 Rs form similar macromolecular complexes.…”
Section: The Abc Of Ip 3 : Where Does It Come From and Where Does It Go?mentioning
confidence: 99%